Biologically relevant unusual cooperative assemblies and fascinating infinite crown-like supramolecular nitrate–water hosts involving guest complex cations in bipyridine and phenanthroline-based Cu(ii) coordination compounds: antiproliferative evaluation and theoretical studies. (22nd April 2021) - Sharma, Pranay; Nath, Hiren; Frontera, Antonio; Barcelo-Oliver, Miquel; Verma, Akalesh K.; Hussain, Sahid; Bhattacharyya, Manjit K.
Abstract : Cytotoxicity in cancer cells with structure activity relationship has been explored in Cu(ii ) compounds involving biologically relevant cooperative assemblies and fascinating crown-like nitrate–water hosts with guest complex cations. Abstract : Two new coordination complexes of Cu(ii ) viz .; [Cu(bpy)2 (NO3 )]NO3 ·5H2 O (1 ) and [Cu(phen)(Hdmpz)Cl2 ]·H2 O (2 ) (bpy = 2, 2′-bipyridine, phen = 1, 10-phenanthroline, Hdmpz = 3, 5-dimethyl pyrazole) have been synthesized and characterized by single crystal X-ray diffraction, electronic spectroscopy, EPR, FT-IR spectroscopy and TGA. The nitrate anion and the water molecules in the lattice of 1 are involved in the formation of unconventional infinite supramolecular crown-like nitrate–water clusters. The unconventional enclathration of guest cationic complex moieties of 1 within the supramolecular nitrate–water crown hosts provides stability to the crystal structure. Crystal structure analysis of 2 reveals the presence of cooperative ternary π-stacked assemblies with enclathration of single guest water molecules in hexameric Cu(ii ) supramolecular host cavities. Theoretical calculations have been performed to analyse the non-covalent interactions in the compounds; focusing on the unusual H-bonding network/anion–π cooperative assemblies in 1 and two different π-stacked cooperative assemblies in 2 . DFT studies reveal that the distribution and orientation of the H-bonds in the cooperative H-bonding network in 1 is the most favoured. The high interaction energies of (π–π)1 and (π–π)2 in π-stacked ternary assemblies of 2 can be attributed to the participation of the entire aromatic surfaces with antiparallel orientations and the cooperative C–H⋯Cl interactions respectively. The in vitro antiproliferative activities of the compounds considering cell cytotoxicity, apoptosis and DNA fragmentation assays reveal significant concentration dependent cytotoxicity in DL cancer cells with nominal effects in normal PBMC cells. The molecular docking and pharmacophore studies established the structure activity relationship of the compounds.